Barystatic sea level change observed by satellite gravimetry: 1993–2022 - Yufeng Nie; Jianli Chen; Guodong Xu; Anno Löcher (Proceedings of the National Academy of Sciences, 2025)
Using time-variable gravity fields determined from satellite laser ranging (SLR) and the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GRACE-FO), we derive three decades of barystatic sea level (BSL) change estimates since 1993, providing a long record of satellite gravimetry-based BSL estimates comparable in duration to satellite altimetry. Over the 1993–2022 altimetry era, the BSL change rate is 1.75 ± 0.59 mm/y (2σ) as observed by SLR. The rate increases to 2.16 ± 0.59 mm/y (SLR) and 2.13 ± 0.38 mm/y (GRACE/-FO) over 2003–2022, mainly due to accelerated ice loss in Greenland since the 2000s. The remarkable agreement between SLR and GRACE/-FO estimates over the joint period cross-validates each other, suggesting that both work well in monitoring BSL changes. We also compare our satellite gravimetry estimates with the sum of individual mass change components (ice sheets, glaciers, and land water storage) obtained from multisource datasets (in situ, remote sensing and geophysical modeling). The differences are within 0.2 mm/y over the three decades, highlighting the global consistency of different techniques for observing Earth’s surface mass changes. Moreover, we reconcile the global mean sea level (GMSL) rise budget using reprocessed altimetry data and updated thermosteric sea level ensembles. From 1993 to 2022, the sum of thermosteric and SLR-based barystatic contributions (3.16 ± 0.64 mm/y) agrees well with altimetry-observed GMSL rate (3.22 ± 0.28 mm/y), suggesting that the GMSL rise budget can be closed within uncertainties over the last three decades.